2019
DOI: 10.1016/j.exphem.2019.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Fetal liver Mll-AF4+ hematopoietic stem and progenitor cells respond directly to poly(I:C), but not to a single maternal immune activation

Abstract: T(4;11) MLL-AF4 acute leukemia is one of the most aggressive malignancies in infant and pediatric populations. Epidemiological and functional studies have highlighted the influence of an overstimulation of the immune system on leukemia development. This study aimed at assessing if the cell-of-origin of t(4;11) MLL-AF4 acute leukemia is sensitive to a viral or bacterial mimic and if maternal immune activation can lead to a full-blown leukemia. To answer this, we used the Mll-AF4 pre-leukemia mouse model that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…We recently described an MLL-AF4 pre-leukemia mouse model that showed a higher selfrenewal and B-lymphoid bias in the Lineage-Sca1 1 c-Kit 1 (LSK) compartment of the fetal liver (FL), but was missing additional factors that would allow development of a full-blown leukemia. [14][15][16] MicroRNAs (miRNAs) are essential regulators of gene expression and key modulators of hematopoiesis and leukemogenesis, but their roles in MLL-AF4-driven leukemogenesis remain elusive. [17][18][19] This study focuses on miR-130b and miR-128a, which we found to be upregulated in the leukemic blasts of MLL-AF4 1 ALL patients, but which had not previously been linked to MLL-AF4 1 ALL.…”
Section: Introductionmentioning
confidence: 99%
“…We recently described an MLL-AF4 pre-leukemia mouse model that showed a higher selfrenewal and B-lymphoid bias in the Lineage-Sca1 1 c-Kit 1 (LSK) compartment of the fetal liver (FL), but was missing additional factors that would allow development of a full-blown leukemia. [14][15][16] MicroRNAs (miRNAs) are essential regulators of gene expression and key modulators of hematopoiesis and leukemogenesis, but their roles in MLL-AF4-driven leukemogenesis remain elusive. [17][18][19] This study focuses on miR-130b and miR-128a, which we found to be upregulated in the leukemic blasts of MLL-AF4 1 ALL patients, but which had not previously been linked to MLL-AF4 1 ALL.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, recent publications have reported that using fetal cell types and carefully regulated levels of MLL fusion oncoproteins may improve the lineage fidelity of murine MLL -r leukemia model systems. In one case, inducible Mll -AF4 knock-in models that must be kept on a mixed genetic background exhibit ~30% B-ALL with many still succumbing to AML [ 64 , 65 ] Using knock-in models from the Rabbitts’ laboratory, several groups have found that progenitors exhibit an embryonic period of sensitivity to Mll -AF4 or Mll -ENL transformation [ 66 , 67 ]. For example, Malouf and Ottersbach [ 66 ] and Barrett et al [ 68 ] reported that fetal liver lymphoid-primed progenitors exhibit a preleukemic phenotype dependent on Mll -AF4 expression but fall short of producing full-blown B-ALL.…”
Section: Model Systems For Studying Mll -R B-all Evolution Under Car T Cell Pressurementioning
confidence: 99%
“…In one case, inducible Mll -AF4 knock-in models that must be kept on a mixed genetic background exhibit ~30% B-ALL with many still succumbing to AML [ 64 , 65 ] Using knock-in models from the Rabbitts’ laboratory, several groups have found that progenitors exhibit an embryonic period of sensitivity to Mll -AF4 or Mll -ENL transformation [ 66 , 67 ]. For example, Malouf and Ottersbach [ 66 ] and Barrett et al [ 68 ] reported that fetal liver lymphoid-primed progenitors exhibit a preleukemic phenotype dependent on Mll -AF4 expression but fall short of producing full-blown B-ALL. Okeyo-Owuor et al [ 67 ] similarly found, using a distinct MLL-ENL knock-in, that a perinatal progenitor exhibited the peak sensitivity to MLL-ENL -mediated transformation; however, AML was the outcome in these mice.…”
Section: Model Systems For Studying Mll -R B-all Evolution Under Car T Cell Pressurementioning
confidence: 99%
“…The placenta as an HSC niche is unique in its exposure to, and possible influence from, exogeneous signalling through its main function as the foetal-maternal interface. On the basis of the Mll-AF4 + VEC-Cre + pre-leukaemic mouse model we discussed earlier in this Review, our group developed a model system to investigate whether inflammatory signals of maternal origin provide the necessary trigger to cause full leukaemia transformation ( Malouf and Ottersbach, 2019 ). This hypothesis was supported by evidence found in non-infant paediatric ALL, where infections can lead to key secondary mutations that facilitate leukaemogenesis, and has recently been reviewed by Mel Greaves ( Greaves, 2018 ).…”
Section: Aspects Of Niche Involvement In Infant Leukaemiamentioning
confidence: 99%
“…We then injected the viral mimic polyinosinic:polycytidylic acid [poly(I:C)] into pregnant dams at the same time point as in the in vitro assay. This treatment, indeed, induced an appropriate immune activation in the pregnant dams but was insufficient to cause leukaemic transformation in the resulting pups ( Malouf and Ottersbach, 2019 ).…”
Section: Aspects Of Niche Involvement In Infant Leukaemiamentioning
confidence: 99%